Teknik Pengujian Kinerja Algoritme Relay Jarak Menggunakan DIgSILENT - Nanang Rohadi; Nendi Suhendi; Liu Kin Men (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2021)
This paper presents a novel technique of testing to evaluate the performance of the transmission line protection relay algorithms (model SEL-421 distance relay) using DIgSILENT. The purpose of this publication is to provide an understanding of using DIgSILENT software for testing protection relays. The accuracy of the fault impedance measurement algorithm due to the influence of the system uncertainty factor can be simultaneously observed and tested automatically. The effects of the fault resistance and the power flow angle are considered as uncertainty factors. In the proposed method, the fault simulation on the transmission line is carried out at a number of different fault locations with factors are varied based on the value of the sample parameter and changed simultaneously to see the effect of relay performance. A random sample of parameters is generated over a certain range of values. Automatic testing has been applied through an algorithm developed with DIgSILENT’s DPL (DIgSILENT Programming Language). The examples presented in this publication explaining the proposed methods of testing which can also be used to their practical use. In this publication, the method for testing distance relay has been successfully implemented through a combination of DIgSILENT and MATLAB.